Engineering and innovative materials VI : selected, peer reviewed papers from the 6th International Conference on Engineering and Innovative Materials (ICEIM 2017), September 3-5, 2017, Tokyo, Japan - Ohashi, Takahiro (Mechanical engineer); Yahaya, Muhammad (Diffusion and defect data. Defect and diffusion forum, 2018)
This book consists of the papers that were introduced at the 6th International Conference on Engineering and Innovative Materials (ICEIM 2017, Tokyo, September 3-5, 2017) and we hope that this collection will be interesting and useful for many specialists from the area of materials science in the various branches of production. Polymers, Composites, Metals, Alloys, Photovoltaic Materials, Building Materials, Materials Processing, Mechanical Properties, Chemical Technologies, Biotechnologies, Environmental Engineering Materials Science.